2014
DOI: 10.1021/ma501862a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Decreased Moisture Uptake in Ortho-Methylated Di(cyanate ester) Networks

Abstract: Decreases of up to 50% in the moisture uptake of polycyanurate networks based on 2,2-bis(4-cyanatophenyl)propane (BADCy) and 1,1-bis(4-cyanatophenyl)ethane (LECy) were observed when analogous networks containing a single methyl group ortho-to each aryl−cyanurate linkage were prepared by reduction and acid-catalyzed coupling of salicylic acid followed by treatment with cyanogen bromide and subsequent cyclotrimerization. The differences in water uptake were observed despite similar decreases in packing fraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 38 publications
8
39
0
Order By: Relevance
“…23 -25 Water uptake can be alleviated in part through CE monomer development and the incorporation of functional groups that inhibit water absorption through steric or hydrophobic interactions. 26 For example, our research group and others have shown that incorporating some degree of fluorination within CE monomers results in CEs that display some of the lowest water uptake reported to date. 27,28 Additionally, it has been shown that high conversions of the cyanate groups yields networks with more desirable physical properties, including reduced water uptake.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…23 -25 Water uptake can be alleviated in part through CE monomer development and the incorporation of functional groups that inhibit water absorption through steric or hydrophobic interactions. 26 For example, our research group and others have shown that incorporating some degree of fluorination within CE monomers results in CEs that display some of the lowest water uptake reported to date. 27,28 Additionally, it has been shown that high conversions of the cyanate groups yields networks with more desirable physical properties, including reduced water uptake.…”
Section: Introductionmentioning
confidence: 93%
“…A brief review of the current literature demonstrates that the mechanism of network hydrolysis appears to be multifaceted and increased water uptake has been assigned to detrimental effects of catalysts, pore sizes within the network that can accommodate water molecules, incomplete curing of the cyanate groups and others . Water uptake can be alleviated in part through CE monomer development and the incorporation of functional groups that inhibit water absorption through steric or hydrophobic interactions . For example, our research group and others have shown that incorporating some degree of fluorination within CE monomers results in CEs that display some of the lowest water uptake reported to date .…”
Section: Introductionmentioning
confidence: 99%
“…The networks chosen for comparison have all been analyzed using either identical or nearly identical protocols in our laboratories, thereby helping to ensure that comparisons reflect meaningful differences. Table 1 lists the properties of interest for all of these materials, along with the original source publications (9)(10)(11)(12)(13)(14)(15), where available. In some cases, as noted in the table, publication is in progress.…”
Section: Materials and Data Sourcesmentioning
confidence: 99%
“…Dai et al reported an epoxidized polysiloxane with amino silicone and used it as a modifier to effectively reduce the dielectric constant of CE resin . Guenthner et al reported the preparation of a novel silyl cyanate monomer from bis(4‐cyanophenyl) dimethylsilane (Simcy), and moisture absorption of the as‐prepared CE resin was reduced by 50%, when compared with pure CE resin . Gu's group synthesized high‐quality and stable fluoride‐containing compound 2‐((3‐(trifluoromethyl)phenoxy)methyl) oxirane (TFMPMO), and the results showed that TFMPMO was gifted with lower moisture absorption than cyanate ester resins .…”
Section: Introductionmentioning
confidence: 99%